2019
DOI: 10.1002/adma.201970265
|View full text |Cite
|
Sign up to set email alerts
|

Flexible Electronics: Highly Stretchable Metallic Nanowire Networks Reinforced by the Underlying Randomly Distributed Elastic Polymer Nanofibers via Interfacial Adhesion Improvement (Adv. Mater. 37/2019)

Abstract: In article number 1903446, Kenjiro Fukuda, Takao Someya, and co‐workers demonstrate a simple fabrication approach for porous nanomesh‐type elastic conductors consisting of Ag nanowires and polyurethane nanofibers. The conductors simultaneously achieve high conductivity (9190 S cm−1), high stretchability (310%), and good durability. Without any adhesive gel/tape, the conductors can be utilized as skin‐attachable strain sensors and dry biosignal‐sensing electrodes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 0 publications
1
12
0
Order By: Relevance
“…The peeling test further demonstrated that the adhesion at the interface was enhanced because of the presence of hydrogen bonds between the CO groups of PVP and OH groups of gelatin (Figure S3). This enhanced adhesion between conductors and substrates was previously reported to enhance the mechanical properties of the stretchable conductors . As a result, we can stretch our stretchable transient conductor to 100% without any failure and with good recovery (Figure e).…”
Section: Resultssupporting
confidence: 71%
See 2 more Smart Citations
“…The peeling test further demonstrated that the adhesion at the interface was enhanced because of the presence of hydrogen bonds between the CO groups of PVP and OH groups of gelatin (Figure S3). This enhanced adhesion between conductors and substrates was previously reported to enhance the mechanical properties of the stretchable conductors . As a result, we can stretch our stretchable transient conductor to 100% without any failure and with good recovery (Figure e).…”
Section: Resultssupporting
confidence: 71%
“…This enhanced adhesion between conductors and substrates was previously reported to enhance the mechanical properties of the stretchable conductors. 11 As a result, we can stretch our stretchable transient conductor to 100% without any failure and with good recovery (Figure 1e).…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…Reproduced with permission. [ 11 ] Copyright 2019, Wiley‐VCH. c) SEM image of the patterned Ag nanofibers/NWs hybrid electrode (top) and schematic diagram of the multiplexed fingerprint sensor (bottom).…”
Section: Overview Of Low‐dimensional Nanomaterialsmentioning
confidence: 99%
“…[ 5b ] They have a conjugated backbone and become highly conductive when in doped state. [ 6 ] Doping is carried out by oxidizing or reducing the conjugated polymers. As the charge transport is usually dominated by the interchain charge carrier hopping, the conductivity of ICPs greatly depends on the crystallinity as well.…”
Section: Icps For Bioelectronicsmentioning
confidence: 99%